Controlled time release and leaching of silver nanoparticles using a thin immobilizing layer of aluminum oxide - Brobbey KJ; Haapanen J; Gunell M; Toivakka M; Mäkelä JM; Eerola E; Ali R; Saleem MR; Honkanen S; Bobacka J; Saarinen JJ (ELSEVIER SCIENCE SA, 2022)
Silver nanoparticles are widely used as antibacterial agents in consumer products. There have been concerns about the environmental exposure and their toxic effect to organisms such as fish. Studies have quantified the release of silver from various products including textiles and plastics that use silver as an antibacterial agent, yet there is no unified standard for the measurement of silver release. Additionally, there is limited information about the release of silver from glass surfaces coated with silver nanoparticles. While immobilizing silver to substrates will ultimately reduce environmental exposure, deliberately controlling silver release will also reduce the amount of silver released into the environment. In this study, silver nanoparticles were synthesized and deposited onto glass using an aerosol pyrolysis process, i. e. the Liquid Flame Spray. The deposited silver nanoparticles were further coated with a thin layer of aluminum oxide that was fabricated by atomic layer deposition. The leaching of silver from the coated glass was measured in water over a period of six days. The results show that a 15 nm thin layer of aluminum oxide is able to inhibit the release of silver up to 48 h, thereby providing a way to control the release of silver in time.